USING PICTURES IN TEACHING VOCABULARY TO YOUNG LEARNERS.: TEACHING VOCABULARY TO YOUNG LEARNERS. - Elmurodova, Zuli; Ruzmetova (Журнал иностранных языков и лингвистики, 2025)
Vocabulary knowledge is often viewed as a critical tool for second language learners because a limited vocabulary in a second language impedes successful communication. Teaching vocabulary is an essential part of language learning that helps students build their linguistic skills and comprehension.